Agency, sentiment, and risk and uncertainty: Fears of job loss in 8 European countries - Gordon L. Clark (ZFW - Advances in Economic Geography, 2022)
How people assess their prospects and act accordingly is anchored in time and space. But context is only half the story. Human beings share predispositions in favour of the here and now, discounting the future, and risk aversion. This paper provides a framework for integrating cognition with context in economic geography focusing upon agency, resources, and risk and uncertainty in European labour markets. In doing so, it seeks to avoid essentialising the individual while ensuring that the resulting framework does not leave individuals as cyphers of time and place. The framework is illustrated by reference to individual's assessments of the consequences of technological change for their employment prospects in a multicountry European setting. Implications are drawn for a behavioural economic geography that is policy relevant.
Keywords: 330